Aypate Archaeological Complex: a little understood cultural heritage of the highlands of Piura, Peru - Amirpasha Tirado-Kulieva, Vicente (2022)
The Aypate Archaeological Complex is a National Cultural Heritage designated by the Ministerio de Cultura and inscribed as a World Heritage Site by the United Nations Educational, Scientific and Cultural Organization (UNESCO), but it is little valued. The purpose of this study was to describe the characteristics of Aypate, revealing its high archaeological and tourism potential. First, a brief description was given about the significance of Aypate, its location and the functionalities that made it a relevant Inca settlement due to its role in the economic development and overall control of the region. Its history was detailed, from the evidence of its existence, its discovery and its declaration as a national and world heritage site. The architectural characteristics of Aypate and its representative buildings, including their uses, were also mentioned. Emphasis was placed on social vulnerability, of Aypate due to the isolation of the State, preventing the use of its qualities. Although the panorama has improved and the residents have the protagonism they deserve, there is still resentment. Finally, it was stressed that Aypate was an administrative center and its tourist attraction is an added value. Tourists should know that they will not find the typical monument, but ruins that will make their imagination explode to reconstruct their past, the real attraction of Aypate. Therefore, tourist’s satisfaction depends on their perception and imagination.